PENGARUH LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA - Renil Septiano; Rysha Mulyadi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine the effect of liquidity measured by the current ratio (CR), and firm size measured by the natural logarithm (Ln) of total assets against financial performance in companies in the otomotiver from 2017-2021. The method of determining the sample used was purposive sampling. The sample used was 9 companies. The data analysis technique used is panel data regression analysis consisting of chow test, hausman test, using Eviews 9.0 software. Partially liquidity (CR) had a significant negative effect on financial performance (ROA). Whereas company size (Ln Total Assets) did not have a significant effect on financial performance (ROA).